Metamorphosis of a Transregional Traffic Junction: Lviv's Railway Stations in context of Eastern European Urban Development (KULT_online, 2023)
A scientific work with high source reference: Nadja Weck’s dissertation Eisenbahn und Stadtentwicklung in Zentraleuropa am Beispiel der Stadt Lemberg (Lwów, L‘viv) is an important contribution to Eastern European infrastructural history.